Surface Modulation of Fe3O4 Confined in Porous Molybdenum‐Based Nanoplatform for Enhanced Hydrogen Production. Issue 2 (7th December 2022) - Nwaji, Njemuwa; Akinoglu, Eser Metin; Lin, Qin; Tufa, Lemma Teshome; Sharan, Abhishek; Singh, Nirpendra; Wang, Xin; Giersig, Michael; Lee, Jaebeom
Abstract : The integration of different precursor components to form single nanostructures via one‐step synthesis process is mostly restricted by the compatibility and complexity of components. Herein, a highly uniform, spherical, hollowed, and hierarchical iron oxide‐wrapped Mo–polydopamine is synthesized using a one‐pot liquid‐phase reaction at room temperature. Mo2 C is doped with Fe3 O4 to harness the rich electrons in Fe dopants for effective lowering of the unoccupied d ‐orbitals in Mo. The surface conductivity of the as‐prepared nanostructures is enhanced by decorating them with gold nanoparticles utilizing strong interaction of Au and amine. The nanocomposites are converted into carbidic hollowed structures via an annealing process without any distortion in morphology. The well‐organized structure and nanosize of the particles provide efficient catalytic performance for hydrogen evolution reaction in acidic media. MoFe–C@Au exhibits a very positive onset potential of 2 mV, low Tafel slope of 50.1 mV dec −1, and remarkable long‐term stability. Abstract : The in situ entrapment of ultra‐small Fe3 O4 nanoparticles inside hierarchical molybdenum polydopamine is hereby described. Functional group chemistry is utilized to decorate the surface of the nanoplatform with gold nanoparticles. The prepared nanoplatform shows efficient catalytic properties with positive onset potential of 2 mV, low Tafel slope of 50.1 mV dec −1, remarkable long‐term stability, and enhanced hydrogen evolution catalytic property for hydrogen.